2014
DOI: 10.1017/s0022029914000211
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of milking frequency on milk yield, milk composition, somatic cell count and milk protein profile in dairy goats

Abstract: Goats in Canary Islands are milked once a day by tradition, but in most countries with high technology on farms, goats are milked twice a day, which is known to improve milk yield. Therefore it is important to know whether the increase of milking frequency can improve the production without impairing milk quality. The objective of this study was to investigate the short term effects of three milking frequencies on milk yield, milk composition, somatic cell count (SCC) and milk protein profile in dairy goats tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…On average, the goat’s milk in this study had a higher content of fat and protein than those reported by other authors using comparable breeds [26,27,28,29,30,31,32]. However, the milk had similar lactose levels to those reported by several authors [26,28,30], but lower levels than those reported by others [29,31,33].…”
Section: Discussionsupporting
confidence: 60%
“…On average, the goat’s milk in this study had a higher content of fat and protein than those reported by other authors using comparable breeds [26,27,28,29,30,31,32]. However, the milk had similar lactose levels to those reported by several authors [26,28,30], but lower levels than those reported by others [29,31,33].…”
Section: Discussionsupporting
confidence: 60%
“…The variation in MY and milk composition among different breeds of sheep and goats has been observed by several authors. Such factors include genetics ( Clark and Sherbon, 2000 ; Greyling et al, 2004 ; Koutsouli et al, 2017 ; Lôbo et al, 2017 ; Montaldo et al, 2010 ; Salvador et al, 2016 ); nutrition ( Baldin et al, 2014 ; Bernard et al, 2009 ; Bernard et al, 2012 ; Carnicella et al, 2008 ; Catunda et al, 2016 ); parity and number of lambs born ( Ahuya et al, 2009 ; Carnicella et al, 2008 ; Salvador et al, 2016 ); days after parturition ( Koutsouli et al, 2017 ); milking frequency ( Koutsouli et al, 2017 ; Kremer and Rosés, 2016 ; Torres et al, 2014 ); environmental conditions ( Arias et al, 2012 ; Peana et al, 2017 ); and other physiological status ( Caroprese et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that no histological and pathological differences in the mammary glands or other evidence of mastitis were detected on fresh udder half tissues of goats with low (950.000 cells/mL), medium (1.500.000 cells/mL), and high (3.300.000 cells/mL) SCC. The SCC in goat milk may be affected by numerous factors such as stage of lactation, estrus, milking routine (13,14). Therefore, regardless of intramammary infection status, high SCC in raw goat milk, which result in low fat content, might have cause economical losses during ice cream manufacture.…”
Section: Results and Conclusionmentioning
confidence: 99%